Intelligent Face Recognition - Qureshi, Akram; Kajla, Ashok (International Journal of Computer Sciences and Engineering, 2025)
Face recognition has been an important and hard problem in computer vision application. Recently, haar cascade method has proven to be an effective method for face recognition. In this thesis, a simple and powerful approach is developed for real time multi face recognition system. A threefold stage application is developed. in the first stage face detection is done by using Haar cascade. In second stage, Haar cascade features are stored in the memory and compare with the data base faces. In third stage the matched database face is recognized for the query face and displayed with recognized face name. The three stages are mentioned as face detection, feature extraction storage & comparison and at last face recognition. The experimental results for real time multiple recognition system is shown and elaborates the benefit of using the described approach.